Gambaran Perawatan Luka pada Pasien Fraktur Pasca Operasi Di RSUD Kota Makassar - Ernasari, Ernasari; Amir, Haeril (PT.Mantaya Idea Batara, 2021)
Wound care in postoperative fracture patients is a crucial aspect in the healing process and prevention of complications. Poorly treated postoperative wounds can lead to infection, delayed healing, and impaired limb function. This study aims to provide an overview of wound care practices applied to postoperative fracture patients, including procedures, frequency, patient and family involvement, and obstacles faced during care. The method used was a descriptive study with a quantitative approach through direct observation and semi-structured interviews with fracture patients undergoing outpatient and inpatient care. The results showed that most patients received wound care according to standards, but there were still obstacles in self-education, compliance with control schedules, and limited family knowledge about signs of infection. The conclusion of this study emphasises the importance of improving systematic and continuous wound care education to support the healing process and improve patient independence.